PENGARUH OPINI AUDIT TAHUN SEBELUMNYA, UKURAN PERUSAHAAN, LIKUIDITAS, PROFITABILITAS, DAN SOLVABILITAS TERHADAP OPINI GOING CONCERN (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014–2018) - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA; Rodiyatan Mardiyah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
This study examines the effect of the previous year's audit opinion, company size, liquidity, profitability, and solvency on going-concern audit opinion on mining companies listed on the Indonesia Stock Exchange for the period 2014-2018. Data were tested using logistic regression. The result of this research is that the previous year's audit opinion variable partially affects going-concern audit, while company size, liquidity, profitability and solvency, respectively, partially have no effect on going-concern audit opinion. Then simultaneously, the five independent variables affect the going concern audit opinion.